Building Bridges of Tolerance Through Multicultural Education in Junior High Schools - Hakim, Arif Rohman; Syafi’i, Akhmad; Fauzia, Eva (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
In the era of globalization and increasing cultural diversity, society needs to build bridges of tolerance to create a harmonious environment. Multicultural education has been recognized as an effective way to achieve this goal. This research aims to explain the concept of 'Building Bridges of Tolerance Through Multicultural Education, 'focusing on its implications and benefits in overcoming cultural, religious, and identity differences in society. Through a qualitative approach, this research outlines the concept of building bridges of tolerance through multicultural education, exploring relevant goals, principles, and approaches. Data collection techniques were conducted using in-depth interviews and observations of students and teachers at SMPIT Ibnu Khaldun in Cirebo n. The findings of this research illustrate that multicultural education plays an important role in forming an inclusive mindset and fostering mutual respect between individuals from different cultural backgrounds. By realizing the importance of multicultural education, we welcome positive changes toward a more harmonious and tolerant society. The research results show that a multicultural education approach not only forms students into individuals with broad cultural knowledge but also individuals who can interact with deep respect for cultural differences. Multicultural education makes students more tolerant, open-minded, and ready to contribute to an increasingly diverse society.